Analysis of Intrinsic Structure and Educational Values in Folklore in Sape District, Bima Regency - Muh. Sya’ban; Munirah; Abd. Rahman Rahim (RETORIKA: Jurnal Ilmu Bahasa, 2022)
This study aims to describe (1) the intrinsic structure of folklore in Sape District, Bima Regency; and (2) the educational value of folklore in Sape Subdistrict, Bima Regency. This research was conducted in three villages, Sape Subdistrict, Bima Regency, which consisted of Jia Village, Sari Village, and Sangia Village. This study uses a qualitative approach with descriptive research with data collection techniques through observation, interviews, document analysis. The data analysis technique uses the Miles, Huberman, and Saldana technique which consists of three stages, namely: data reduction, data presentation, and drawing conclusions. Testing the validity of the data in this study used method triangulation and theoretical triangulation. The results showed that: (1) the results of the three folk tales of Sape Subdistrict, Bima Regency have intrinsic value. The intrinsic value of the folklore of Tabe Bangkolo, Wadu Sura, and Nanga Nur includes themes, characters and characterizations, plot, setting, and mandate; and (2) the results of the research on the educational value (education) of the three folk tales of Sape Subdistrict, Bima Regency, found the value of religious/religious education, the value of moral education, the value of traditional education, and the value of historical education.